1986
DOI: 10.3354/meps029289
|View full text |Cite
|
Sign up to set email alerts
|

Physical control of the horizontal patchiness of sea-ice microalgae

Abstract: Factors controlling the horizontal distribution of sea-ice microalgae were studied in Southeastern Hudson Bay and adjacent Manitounuk Sound (Canadian Arctic). Both large (-30 km) and small (0.3 to 500m) scales of variability were investigated. Results showed that salinity was the most important factor controlling large scale distribution of the ice-microalgal biomass, through its effect on the structure of the ice (surface available for colonization). Variation in the thickness of the snow-ice cover, which det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
100
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 18 publications
15
100
3
Order By: Relevance
“…Other investigators have shown that photosynthetic microbes can inhabit the interior, upper surface, and lower surface of ice, and tend to be most concentrated on the bottom surface (Welch et al, 1988;Cota et al, 1991;Frenette et al, 2008;Boetius et al, 2013). Traditionally, investigators have argued that ice-associated communities are most prevalent in ice formed from seawater; as salinity increases, the volume of unfrozen brines within the ice that the microbes can inhabit increases, and the bottom surface of the ice becomes more uneven, increasing bottom algal settlement efficiency (Legendre et al, 1981;Gosselin et al, 1986). However, more recently, investigators have also found algae growing within and on the bottom of freshwater ice in lakes and rivers, including locations in Canada such as the Great Lakes and the St. Lawrence River (Bondarenko et al, 2006;Frenette et al, 2008;Twiss et al, 2012;D'souza et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Other investigators have shown that photosynthetic microbes can inhabit the interior, upper surface, and lower surface of ice, and tend to be most concentrated on the bottom surface (Welch et al, 1988;Cota et al, 1991;Frenette et al, 2008;Boetius et al, 2013). Traditionally, investigators have argued that ice-associated communities are most prevalent in ice formed from seawater; as salinity increases, the volume of unfrozen brines within the ice that the microbes can inhabit increases, and the bottom surface of the ice becomes more uneven, increasing bottom algal settlement efficiency (Legendre et al, 1981;Gosselin et al, 1986). However, more recently, investigators have also found algae growing within and on the bottom of freshwater ice in lakes and rivers, including locations in Canada such as the Great Lakes and the St. Lawrence River (Bondarenko et al, 2006;Frenette et al, 2008;Twiss et al, 2012;D'souza et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…9) is very large compared to that of other flux methods (Berg et al, 2007) and is expected to integrate most variability commonly observed at the ice-water interface (McMinn and Ashworth, 1998; Rysgaard et al, 2001). It has been suggested that to include all horizontal variations in light, algal biomass and algal activity it is necessary to measure across distances of 20 to 100 m as dictated by variations in light availability below melting ponds and snow drifts (Gosselin et al, 1986;Rysgaard et al, 2001;Søgaard et al, 2010). Figure 9 shows the size of the footprint to be over 60 m long, and therefore it integrates over most of this variability.…”
Section: Discussionmentioning
confidence: 99%
“…The techniques presently used to study sea-ice primary production sample at either one point on the ice surface or within an ice core, though algal patchiness and activity have been reported to vary across a much wider range (Gosselin et al, 1986;Rysgaard et al, 2001). This may lead to misrepresentation of the actual sea-ice environment and requires that many replicates are taken over a large area.…”
Section: H Long Et Al: Oxygen Exchange and Ice Melt By Eddy Corrmentioning
confidence: 99%
“…This relationship explains the similar patch sizes observed for snow and sea ice algae biomass on the same study sites. Between study sites, however, patch sizes had a large range between 5 and 90 m, which was the result of differences in the snow distribution and drifting patterns over relatively level FYI (Gosselin et al, 1986;Rysgaard et al, 2001;Granskog et al, 2005;Søgaard et al, 2010). In contrast, the undulating surface topography of MYI plays an important role in the distribution of snow, which has been linked to the presence of high ice algal chl a biomass at the bottom of thick MYI hummocks with little or no snow cover .…”
Section: Introductionmentioning
confidence: 97%
“…It is within this spatial range that many sea ice and snow properties (such as thickness, porosity, temperature) can vary, which can have a large influence on light availability, ice melt and growth, nutrient availability, and therefore, the spatial distribution of ice algae. Typical patch sizes of snow have been reported in the range 20-25 m (Gosselin et al, 1986;Steffens et al, 2006). Surface properties such as albedo have patch sizes of ∼10 m (Perovich et al, 1998;Katlein et al, 2015a) and sea ice draft can vary at scales of around 15 m (Katlein et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%